Community-Based Education Oriented Towards Socio-Cultural And Religious Values - Eni Desfitri; Hefni Hefni; Yanti Sriwahyuni; Nora Afnita; Joni Indra Wandi (Institut Agama Islam Sumatera Barat, 2024)
Education is a fundamental pillar in building sustainable and competitive societies in the era of globalization. Amid the dynamics of social change, it is important for the education system to consider socio-cultural and religious values as a strong foundation in the learning process. This article aims to propose a community-based education approach that integrates socio-cultural and religious values as primary elements. This approach not only emphasizes the transfer of knowledge and skills but also the formation of strong character and deep understanding of the cultural identity of society. Using qualitative conceptual analysis and literature review methods, this research explores the relevance and urgency of education rooted in socio-cultural and religious values in the context of increasingly multicultural societies. In the process, this article presents implementation strategies that can be adopted, identifies potential challenges, and outlines the benefits that can be gained from the proposed education approach. It is hoped that the results of this research can provide deeper insights into the role of education in strengthening cultural identity and promoting social harmony in diverse societies